A new species of deepwater tilefish (Percoidea: Branchiostegidae) from the Philippines, with a brief discussion of the status of tilefish systematics - Dooley, James K.; Iwatsuki, Yukio (Zootaxa, 2012)
A new rare species of deepwater Branchiostegus is described from two specimens collected from Bayangas, Laiya, Philippines(130 38.5’ N, 1210 25.6’ E). A total of four specimens were caught by hook and line in 2009 and 2011 between 210–220 m overa rocky-sand bottom, only two were preserved. The species may also be endemic to the Philippines and inhabit burrows as dothe other known species of this genus. The combination of the following characters distinguish the new species from its conge-ners: prominent dark predorsal ridge bordered by bright yellow-orange background (only B. semifasciatus from West Africahas a more prominent and dark predorsal ridge, but the ridge has no underlying orange-yellow colour), a great body depth (28–29% SL; other species of Branchiostegus, usually 27% SL) longer head length (30–31% SL; other species of Branchiostegus,usually 28%), greater head depth (26–27% SL; other species of Branchiostegus, usually 26% SL); long pre-dorsal length (35%SL; other species of Branchiostegus, usually 32% SL), and distinctive body, head and caudal fin colouration; skin over dorsal tips of branchiostegals characteristically bright yellow. A brief discussion of the status of tilefish systematics is included.